KEMBALIKAN DUNIA KECILKU: STUDI EKSPOLRATIF MANFAAT LAGU ANAK-ANAK ERA 90AN BAGI PERKEMBANGAN ANAK - LULU' SUKMA WARDANI (Al-Tazkiah : Jurnal Bimbingan dan Konseling Islam, 2019)
The role of parents is very important for the development of children, especially in the midst of the rapid growth of electronic media and technology. The right stimulus is needed for the child's development so that they can develop properly, both in the aspects of creativity, imagination, character and so on. In this case, the stimulus that is close to the child can be in the form of a song, given the influence of the presence of the song is very quickly accepted by the child. However, the songs contained today contain more content that tells the content of the world of adolescence to adulthood and away from the world of children. Children's songs that were popular before the 90s are becoming increasingly rare to hear again. This research is intended to dig deeper into the meanings contained in children's songs viewed from the psychological aspects using a qualitative paradigm with a phenomenological approach through text analysis. The research method used was documentation study, by collecting several songs as samples which were then analyzed. The analysis was carried out on popular children's songs before the 90s. In supporting data credibility, this study uses subject triangulation to minimize subjective data processing results. The results found that in some of the children's songs analyzed, the children's songs are following the child's development and there are positive values ??related to the values ??needed in the child's developmental tasks.